Uncertainty in the Dynamics of Fish Prices in Social-Ecological System of Neritic Tuna Fisheries (Case Study: Pasongsongan, Sumenep) - Ashma Hanifah; Luky Adrianto; Zairion Zairion (Faculty of Fisheries and Marine Science, Brawijaya University, 2022)
People use fish to meet their needs. Fish utilization and economic activities in the neritic tuna’s fishery system at Pasongsongan were an effort to achieve social welfare. However, the uncertainty surrounding economic activities caused a risk to fishermen's income stability. Those are conducted in this research to identify the elements of social-ecological system of neritic tuna fisheries at Pasongsongan and to assess the risk based on the uncertainty of the daily fish prices. Identification of the elements of the social-ecological system followed the framework by Ostrom, while the uncertainty was analyzed by monte carlo simulation using R-Studio. The results showed six elements of Resource System, three elements of Resource Units, one element of the Governance System, and three elements of Resource Actors. The interaction between elements is fishing productivity and information exchange. The montecarlo simulation showed the fish price determination method contains uncertainty with a greater risk in the daily fish price of kawakawa or komo (Euthynnus affinis) compared to frigate tuna (Auxis thazard), with standard deviation values respectively IDR 8.255 and IDR 6.251. Fish measurement cause the uncertainty of daily fish prices without using validated measuring; therefore, fish weight measurement infrastructure needs to increase pricing considerations accuracy objectively.